2005
DOI: 10.1534/genetics.104.038224
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Between Selective Sweeps and Demography Using DNA Polymorphism Data

Abstract: In 2002 Kim and Stephan proposed a promising composite-likelihood method for localizing and estimating the fitness advantage of a recently fixed beneficial mutation. Here, we demonstrate that their compositelikelihood-ratio (CLR) test comparing selective and neutral hypotheses is not robust to undetected population structure or a recent bottleneck, with some parameter combinations resulting in a false positive rate of nearly 90%. We also propose a goodness-of-fit test for discriminating rejections due to direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
314
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(317 citation statements)
references
References 31 publications
2
314
0
1
Order By: Relevance
“…22 In addition, several studies have shown that some demographic scenarios can also cause negative skews in Fay and Wu's H. 42,43 To distinguish between these two possible causes of the pattern, it is useful to consider the pattern of polymorphism in the Memphis genomic region in a wider variety of human populations. Examination of HapMap (phase 3) SNP data from our resequenced region shows five overlapping SNPs that have been genotyped in 10 world populations (excluding the Japanese), including three where the derived allele is at high frequency in our sample (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…22 In addition, several studies have shown that some demographic scenarios can also cause negative skews in Fay and Wu's H. 42,43 To distinguish between these two possible causes of the pattern, it is useful to consider the pattern of polymorphism in the Memphis genomic region in a wider variety of human populations. Examination of HapMap (phase 3) SNP data from our resequenced region shows five overlapping SNPs that have been genotyped in 10 world populations (excluding the Japanese), including three where the derived allele is at high frequency in our sample (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…For example, positive selection driving a mutation to fixation (i.e., a selective sweep) (Maynard Smith and Haigh 1974) may resemble a population bottleneck (Simonsen et al 1995). Conversely, many demographic perturbations are well known to cause unacceptably high rates of false positives for many classical tests for selection (Simonsen et al 1995;Przeworski 2002;Akey et al 2004;Jensen et al 2005;Nielsen et al 2005). Thus, if natural selection has a substantial impact on genome-wide patterns of variation, then many demographic parameter estimates could be biased (Hahn 2008;Gazave et al 2014).…”
mentioning
confidence: 99%
“…We study a bottleneck model to explore the properties of genome scans using parameters that may be relevant for Drosophila melanogaster and also because population bottlenecks severely confound the inference of selection (e.g., Jensen et al 2005). We apply what is currently the state-of-the art method for ''subgenomic'' scans (i.e., less than whole-genome SNP data)-the composite-likelihood method of Kim and Stephan (2002) and the goodness-of-fit (GOF) test of Jensen et al (2005). The former method estimates both the strength and target of selection, assuming the demographic null model of a large, panmictic population, and gives a composite likelihood-ratio test (CLRT) comparing the selective sweep model to the standard neutral model.…”
mentioning
confidence: 99%
“…The former method estimates both the strength and target of selection, assuming the demographic null model of a large, panmictic population, and gives a composite likelihood-ratio test (CLRT) comparing the selective sweep model to the standard neutral model. Jensen et al (2005) proposed a GOF statistic intended to be applied to data sets that reject neutrality following the procedure of Kim and Stephan (2002). They showed that the GOF procedure substantially reduces the false-positive rate under nonequilibrium demographic models and also results in a test statistic with a uniform distribution of P-values when the true model is a single selective sweep occurring in a large, constant-size, panmictic population (the model assumed by the CLRT).…”
mentioning
confidence: 99%
See 1 more Smart Citation